Gravity lost - Sagas, L. M. (Sagas, L. M. Ambit's run novel., 2024)
"L. M. Sagas follows her fast-paced sci-fi adventure Cascade Failure with an equally explosive sequel, Gravity Lost. Everyone's favorite fierce, messy, chaotic space fam is back with more vibrant worlds, and the wildest crew since Guardians of the Galaxy. After thwarting a space station disaster and planetary destruction, the Ambit crew thought turning Isaiah Drestyn over to the Union would be the end of their troubles. Turns out, it's only the start. Drestyn is a walking encyclopedia of dirty secrets, and everyone wants a piece of him--the Trust, the Union, even the Guild. Someone wants him bad enough to kill, and with the life of one of their own on the line, the Ambit crew must jail-break the very man they helped capture and expose some of the secrets he's been keeping before it's too late. In the Spiral, everything has a price. In their fight to protect what they love, Eoan, Nash, Saint, and Jal will confront some ugly truths about their enemies, and even uglier truths about their friends. But nothing will come close to the truths they'll learn about themselves. You can't always fix what's broken ... and sometimes, it's better that way."--